Valorization of purple non-sulfur bacteria biomass from anaerobic treatment of fuel synthesis process wastewater to microbial protein: a means of enhancing food security in arid climates - O.Z. Wada (19459570) (2023)
The global shift from traditional fish farming to aquaculture has created an aquafeed production gap. Hence, the recovery of microbial protein from organic and nutrient-rich agro-industrial wastewaters has been identified as a suitable substitute. However, such waste streams are sparse in arid climes like the Middle East. Thus, this study explores the potential of single-cell protein recovery from a novel waste stream abundant in the region–fuel synthesis process water (FSPW), via anaerobic treatment with purple non-sulfur bacteria (PNSB). The feedstock (COD = 10.3 g/L) amended with essential nutrients was inoculated with a PNSB-dominated mixed culture in replicate 1-L batch fermenters. The wastewater characteristics and microbial biomass assays were performed using standard methods. Around two-thirds of the COD was degraded within 72 h at a rate of 2100 mg L−1d−1, which reduced to about 710 mg L−1d−1 by trial end. Also, total nitrogen levels (90 mg/L) were depleted within 72 h, indicating that nitrogen was a limiting nutrient. In addition, a peak biomass concentration of 1.11±0.037 gvss/L was obtained. Proximate analysis revealed that the biomass consisted of 35% protein, 32% lipid, 16% carbohydrate, 7% ash, 0.5% carotenoids, 0.6% bacteriochlorophylls, and 0.004% coenzyme Q10. Biomass protein’s amino acid profile was comparable to soybean grain and meets dietary requirements for several aquatic livestock. Metal analysis of the biomass and wastewater indicated that nutritionally undesirable metals were undetected. Results show that PNSB not only efficiently degrade FSPW’s organic load but also upcycles the waste to valuable feed constituents, potentially creating a regional circular economy. Other Information Published in: Biomass Conversion and Biorefinery License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s13399-023-04518-w